2019
DOI: 10.1159/000496158
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of p16 Immunohistochemistry and HPV Testing in Fine Needle Aspiration Specimens of the Head and Neck

Abstract: Human papilloma virus (HPV)-related squamous cell carcinoma (SCC) is biologically unique and has a better prognosis than conventional SCC of the head and neck. p16 immunohistochemistry emerged as a valuable surrogate marker for HPV in oropharyngeal SCC. The criteria for a positive p16 result in tissue specimens are well established. However, there is no consensus regarding interpreting p16 staining in cell blocks and other cytology specimens. This review discusses the current evidence on p16 testing in cytolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 51 publications
0
38
1
Order By: Relevance
“…In contrast to false negatives, false positive p16 staining in cellblocks appears to be much less of an issue, and none were noted in a recent literature review by Jalaly et al 22 Although we observed one false positive case in our study, on further investigation, the problem seemed to reside with false negative tissue staining, as confirmatory HPV DNA PCR studies performed on both cytological and surgical material were positive. The reason for the false negative tissue staining in this case remains elusive, but, given the somewhat pale appearance of the section, consideration is given to a pre-analytic issue with fixation or processing.…”
Section: Ta B L E 1 Patient Demographicscontrasting
confidence: 68%
See 1 more Smart Citation
“…In contrast to false negatives, false positive p16 staining in cellblocks appears to be much less of an issue, and none were noted in a recent literature review by Jalaly et al 22 Although we observed one false positive case in our study, on further investigation, the problem seemed to reside with false negative tissue staining, as confirmatory HPV DNA PCR studies performed on both cytological and surgical material were positive. The reason for the false negative tissue staining in this case remains elusive, but, given the somewhat pale appearance of the section, consideration is given to a pre-analytic issue with fixation or processing.…”
Section: Ta B L E 1 Patient Demographicscontrasting
confidence: 68%
“…12 We argued in a previous study and a recent literature review that the optimal cut-off may be in the range of 5%-15%. 19,22 While our current study was retrospective and not designed to determine the best p16 cut-off in cell-blocks, using a cut-off between 5%-15%…”
Section: Discussionmentioning
confidence: 99%
“…After Rb protein is degraded, cell cycle limitation is eliminated and transcription factor E2F is associated with increased p16 (INK4) protein expression. 7 HPV infection is closely related to p16 protein expression in OPSCC. Therefore, in these high-risk tumors, p16 can be used as a surrogate biomarker to detect the presence of HPV infection.…”
Section: Introductionmentioning
confidence: 99%
“…12 Then, p16 immunohistochemistry (IHC) in combination with HPV-DNA detection by PCR has been found to be a powerful indicator of clinical outcome in patients with OPSCC using univariate analysis. 7,13 And previous studies have indicated that p16 may enhance the immunogenicity of dendritic cells (DC) by means of Th1 cytokine secretion and cyclin-dependent pathways. 8 HPV infection can give rise to a very extensive of epithelial lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation